2018
DOI: 10.1016/j.stem.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Stem Cells from PSC-Derived Teratomas Have Functional Regenerative Capacity

Abstract: Derivation of functional skeletal muscle stem cells from pluripotent cells without genetic modification has proven elusive. Here we show that teratomas formed in adult skeletal muscle differentiate in vivo to produce large numbers of α7-Integrin+ VCAM-1+ myogenic progenitors. When FACS-purified and transplanted into diseased muscles, mouse teratoma-derived myogenic progenitors demonstrate very high engraftment potential. As few as 40,000 cells can reconstitute ∼80% of the tibialis anterior muscle volume. Newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(141 citation statements)
references
References 40 publications
3
138
0
Order By: Relevance
“…In the present study, we found MPC induced by Givi exhibited superior migration and proliferation capabilities compared with human myoblasts and control MPC generated by CHIR99021 and FGF. Go analysis further showed upregulation of cell migration related genes enabling them to migrate to distant injured muscle (10). In our data, genes related to migration were significantly upregulated with Givi treatment.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…In the present study, we found MPC induced by Givi exhibited superior migration and proliferation capabilities compared with human myoblasts and control MPC generated by CHIR99021 and FGF. Go analysis further showed upregulation of cell migration related genes enabling them to migrate to distant injured muscle (10). In our data, genes related to migration were significantly upregulated with Givi treatment.…”
Section: Discussionsupporting
confidence: 61%
“…These observations support that Givi-MPC had anti-inflammatory effects upon transplantation in CTX injured muscle suggesting that properties of MPC depend on the source of reprogramming molecule. Besides immediate effects on engraftment and differentiation, the long-term maintenance of newly formed skeletal muscle is ultimately dependent on the ability of the transplanted MPCs to contribute to the skeletal muscle stem cell pool (10). Here we observed Givi-MPC derived Pax7 positive cells under basal lamina upon transplantation, and with subsequent reinjury the Givi-MPC contributed to secondary regeneration in the Mdx/SCID mice.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Moreover, the different differentiation protocols already published for the generation of MPCs from iPSCs will also need to be evaluated for their ability to evade the immune system (Chan et al, 2018;Shelton et al, 2016;van der Wal et al, 2018). It also remains to be determined if the presence of autologous T cells can impact long-term engraftment (more than 4 weeks).…”
Section: Unfortunately the Low Level Of Infiltrating T Cells Preventmentioning
confidence: 99%